Implementasi Aplikasi Sistem Pendukung Keputusan Berbasis Metode SAW untuk Proses Kenaikan Pangkat ASN di Kecamatan Kota Kudus - Maulana, Arya; Darmanto, Eko (JPMTT (Jurnal Pengabdian Masyarakat Teknologi Terbarukan), 2026)
The Civil Servants (ASN) in the Kota Kudus District are a strategic asset in the administration of government, with a total of 135 ASN spread across various public service units. The promotion process, which serves as recognition for employee achievements and dedication, is still conducted manually, relying on document verification by personnel staff. This process requires 7 to 10 working days and is prone to recording errors. This study identifies a key issue: the lack of an integrated and data-driven Decision Support System for the promotion process. As a solution, this research proposes the implementation of a web-based DSS using the Simple Additive Weighting method, which can objectively assess multiple criteria. The system is developed using the Laravel framework with a Model-View-Controller (MVC) architecture and MySQL database. With the implementation of this system, the document verification process can be expedited, data entry errors can be minimized, and promotion reports can be generated automatically and in real-time. It is expected that this system will not only enhance efficiency and accuracy but also promote transparency and accountability in managing the careers of civil servants, while strengthening the application of digital governance in the Kota Kudus Distric.